Pengaruh Pertumbuhan Ekonomi, Tingkat Kemiskinan, dan Tingkat Pengangguran Terbuka Terhadap Indeks Pembangunan Manusia Kalimantan Selatan Tahun 2012-2021 - Fachrani Putri, Nabila; Suherty, Lina (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study aims to analyze the influence of South Kalimantan's Economic Growth, Poverty Rate, and Open Unemployment Rate in 2012-2021. This study used the panel data regression analysis method with quantitative data and the data was operated using the E-Views 10 application. The conclusion from this study is that Economic Growth has a negative and significant effect on the South Kalimantan Human Development Index in 2012-2021. The Poverty Level has a negative and significant effect on the South Kalimantan Human Development Index for 2012-2021. Meanwhile, the Open Unemployment Rate has a positive and insignificant effect on the South Kalimantan Human Development Index for 2012-2021.